Strategi Ayobandung.com Untuk Meningkatkan Partisipasi Masyarakat Dalam Citizen Journalism - Firdaus, Muhammad Arif; Fakhruroji, Moch; Muhaemin, Enjang (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2020)
This study aims to find out how the strategy starts from the planning and implementation determined by Ayobandung.com. As well as what are the criteria for proper news on the media Ayobandung.com. The method used in this study is a case study. The case study method was chosen because the focus of the problem under study is related to mass media institutions as intermediaries in the dissemination of information obtained from netizens. In this study it was found that the strategy of Ayobandung.com in making citizen journalism news consists of, firstly planning citizen journalismis made through holding editorial meetings, secondly Implementation of citizen journalism on Ayobandung.com is by providing signs for news writing, and the three criteria for citizen journalism news published on are news that meet the criteria, news about history, events and uniqueness in the city of Bandung.